Analysis of Development Inequality Between Regions in java and bali : Economic Spatial Approach - Ramadhan, Fadjri; Hidayat, Muhammad; Murialti, Neng (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Economic activities often experience disparities (inequalities) in regional development, this is due to differences in natural resources and geographical conditions in each área area. This study aims to find out which regions experience development inequality. This research uses reference data on Gross Regional Domestic Product and Number of Population in Java and Bali, with a range of 2011 – 2022. The method of measuring development disparity using the Theil One Stage and Two Stage Index. The results of this study show that inequality in Java and Bali occurs mostly in East Java and Bali. With a tendency to increase trend (convergen). So the theory of Neo-classical Hypothesis is in line with this research. And inequality in the region (Whitin Region) has a high inequality value of 210% - 146% from 2019 - 2022, while from the second stage 47% - 46%. The conclusion of this study shows that Java and Bali experience high development inequality, with economic interactions between regions reinforcing the inequality.